2023
DOI: 10.3390/diagnostics13223410
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive Capsulitis of the Shoulder: Current Concepts on the Diagnostic Work-Up and Evidence-Based Protocol for Radiological Evaluation

Riccardo Picasso,
Federico Pistoia,
Federico Zaottini
et al.

Abstract: Adhesive capsulitis is an idiopathic and disabling disorder characterized by intense shoulder pain and progressive limitation of active and passive glenohumeral joint range of motion. Although adhesive capsulitis has been traditionally considered a diagnosis of exclusion that can be established based on a suggestive medical history and the detection of supporting findings at the physical exam, imaging studies are commonly requested to confirm the diagnostic suspicion and to exclude other causes of shoulder pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…It was previously believed that the disease was self-limiting and often resolved within 1 to 2 years of onset. The present study revealed that 40% of patients continue to experience signi cant limitations in shoulder joint mobility even after 2 years, signi cantly impacting their daily activities [5].…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…It was previously believed that the disease was self-limiting and often resolved within 1 to 2 years of onset. The present study revealed that 40% of patients continue to experience signi cant limitations in shoulder joint mobility even after 2 years, signi cantly impacting their daily activities [5].…”
Section: Introductionmentioning
confidence: 57%
“…Although frozen shoulder is a self-limiting condition, it has a prolonged course and causes signi cant pain, which greatly affects the daily lives of patients [5,24]. Early and effective treatment can reduce pain, shorten the duration of the disease, and enhance the quality of life for patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first original research focused on assessing the diagnosis of secondary AC in patients with CT of the rotator cuff. Indeed, the association between CT of the rotator cuff and glenohumeral AC is reported even in recent review articles as a possible and not wholly understood association [22].…”
Section: Discussionmentioning
confidence: 99%
“…While according to the guidelines of the European Society of Musculoskeletal Radiology, a radiological diagnosis of AC can be made only with MRI [22], several studies have recently demonstrated the diagnostic reliability through correct US exams, evaluating the…”
Section: Discussionmentioning
confidence: 99%